The effects of information literacy instruction on business students' job readiness. Issue 3 (3rd July 2022) - Le, Daniel; Graham, Adrienne; Walker, Jeremy; Watson, Marie-Louise
Abstract: The purpose of this study is to examine college student perceptions of information literacy instruction and to what extent library instruction influences students' attitudes in their business research during their job-readiness training through the Panthers Advanced Career Experience (PACE). The findings suggest that library instruction intervention positively influenced and increased confidence in completing the information research for their client-based consultation projects.